Periventricular nodular heterotopias an atypical manifestation of Joubert syndrome - Mishra, Himanshu; Kumar, Amit (Nepal Journal of Neuroscience, 2021)
Joubert syndrome (JS) is characterized by varying degrees of mid and hindbrain malformations. A thickened superior cerebellar peduncle (“molar tooth sign”), varying degree of cerebellar vermian clefting, and an oddly shaped (“bat-wing”) fourth ventricle are essential diagnostic cues on imaging. When JS is associated with renal, ocular, hepatobiliary, or oro-facial abnormalities, the term Joubert syndrome and related disorders (JSRD) is used. We report a classic case of this rare disease in a 5 month old male child who presented to our department for assessment of developmental delay. MRI revealed molar-tooth appearance of midbrain, an abnormally shaped fourth ventricle, and vermian aplasia. Additional findings present in our case were corpus callosum dysgenesis, colpocephaly, generalized cortical atrophy, and periventricular nodular heterotopia. Subsequently, an ultrasound of the abdomen was performed to look for any associated anomalies. It revealed diffuse bilateral echogenic kidneys with attenuated corticomedullary differentiation (likely due to micro cysts in medulla) and few thin-walled peripheral renal cortical cysts. Callosal dysgenesis, colpocephaly, cortical atrophy and cortical heterotopias are less common manifestations of JS/JSRD and periventricular nodular heterotopia has been infrequently reported in cases of Joubert syndrome. Key-words: Joubert Syndrome, MRI, Molar Tooth Sign, Periventricular Nodular Heterotopia, Bilateral Echogenic Kidneys